Մուշեղ Գալշոյանի «Ձեռնքաշ Հերոն» ստեղծագործության բառապաշարի քննություն - Խալաթյան, Գայանե; Աղասյան, Թագուհի
Հոդվածում կատարել ենք Մ. Գալշոյանի «Ձեռնքաշ Հերոն» պատմվածքիբառապաշարի տարբեր շերտերի քննություն՝ համագործածական, ժողովրդախոսակցական, բարբառային բառաշերտերիբառեր,բարբառներին անցածփոխառություններ, օտարաբանություններ, դարձվածքներ, բարդությունների տարբեր տեսակներ, կոչականներ, ձայնարկություններ, որոնք խոսքաշարին հաղորդում են պատկերավորություն, հուզարտահայտչականությունեւոճական մեծ լիցքեր: Վերոնշյալները քննել ենք ինչպես հեղինակի, այնպես էլ կերպարների խոսքում: Առավելաբար կարեւորել ենք կերպարների խոսքի անհատականացումը նրանց բառապաշարի միջոցով: В статье мы провели исследование разных пластов лексики повести М.Галшояна "Ворюга Эро": разговорные, диалектные слова, заимствования, вошедшие в диалекты, иностранные слова, словосочетания, различного рода усложнения, фонемы,придающие образность, эмоциональную выразительность и большие стилистические нагрузки на словарный запас. Мы рассмотрели вышеизложенное как в речи автора, так и в речи персонажей, сделав упор на персонализацию речи героев через их словарный запас.В результате исследования сделаны следующие выводы:1. Были вывалены особенности стиля писателя. В речи автора встречаются нетолько слова, относящиеся к литературному пласту, но и диалектные слова, с помощью которых он приближается к речи созданных им персонажей. In the article, we examined different layers of the vocabulary, which gave the vocabulary imagery and expressiveness, and we examined the above mentioned in the speech of the author and characters.1. As a result of examining the vocabulary of the story, the features of the writer's language became clear to us. We noticed that in the author's speech we find not only words belonging to the literary layer, but also dialect words, with which he approaches the speech of the characters he created.2. In the story, the speech of the characters is dominated by words belonging to folk and dialect layers. Their stylistic manifestations contribute to the image system of the work being more impressive.3. Many words are borrowed from other languages such as Persian, Georgian, Turkish, Assyrian, Arabic, etc. Many of them have been used in speech for a long time and have become assimilated into the language. Barbarisms were also used in the work.4. In order to personalize the speech of the heroes, the author tried to use various idioms in their language, which are the result of national thinking.5. True applications of vocative cases andinterjections give great stylistic charges to the work and create a characteristic of time and space.
Keywords: Լեզվաբանություն